2019
DOI: 10.1155/2019/9367404
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Immune System and Microbiota in Diabetes

Abstract: Diabetes is not a single and homogeneous disease, but a cluster of metabolic diseases characterized by the common feature of hyperglycemia. The pathogenesis of type 1 diabetes (T1D) and type 2 diabetes (T2D) (and all other intermediate forms of diabetes) involves the immune system, in terms of inflammation and autoimmunity. The past decades have seen an increase in all types of diabetes, accompanied by changes in eating habits and consequently a structural evolution of gut microbiota. It is likely that all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 84 publications
0
26
0
4
Order By: Relevance
“…Among the mechanism involved in GM dysbiosis and T2DM is an imbalance in the immune system. GM and its metabolites maintain the balance and function of intestinal T helper 17/regulatory T cell (Th17/Treg) and gut-associated lymphoid tissues (GALT) such as Peyer's patches, mesenteric lymph nodes and isolated lymphoid follicles [73]. GM is essential in helping the immune system to differentiate self from non-self (invaders), and it promotes innate hematolymphoid cells (ILC1, -2 and -3), natural killer (NK) cells, cytotoxic and noncytotoxic cells and helper lymphoid cells synthesis.…”
Section: Immune System In Gm-t2dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the mechanism involved in GM dysbiosis and T2DM is an imbalance in the immune system. GM and its metabolites maintain the balance and function of intestinal T helper 17/regulatory T cell (Th17/Treg) and gut-associated lymphoid tissues (GALT) such as Peyer's patches, mesenteric lymph nodes and isolated lymphoid follicles [73]. GM is essential in helping the immune system to differentiate self from non-self (invaders), and it promotes innate hematolymphoid cells (ILC1, -2 and -3), natural killer (NK) cells, cytotoxic and noncytotoxic cells and helper lymphoid cells synthesis.…”
Section: Immune System In Gm-t2dmmentioning
confidence: 99%
“…Intestinal Th17 cells are able to modulate glucose homeostasis, adipogenesis, control immune tolerance and participate in IR development via a reduction of intestinal RORγt+ and IL-17-producing CD4+ [73,75]. Additionally, various studies demonstrated how GM and its products can regulate the harmony of intestinal Th1/Th2 cells functions.…”
Section: Immune System In Gm-t2dmmentioning
confidence: 99%
“…In particular, structural and functional changes of the intestinal microbiota are present in diabetes, obesity, and metabolic syndrome, and these alterations are believed to activate innate and adaptive immune responses that finally result in the development of overt diabetes. 55 Obesity-associated dysbiosis relates to increased gut permeability, resulting in leakage of microbial products and oral antigens across the gut epithelium. The latter, together with excessive lipid accumulation and dead adipocytes, represent potential sources of antigens that trigger the activation of B-and T-cells, a process occurring either in the lymph nodes or in the adipose tissue.…”
Section: Gut Microbiota and T2dmentioning
confidence: 99%
“…Gut microbiota has an important role in the regulation of metabolism. Although causality between dysbiosis and T1D has not been proved yet in humans because long-term placebo-controlled trials are missing, literature data suggested a role of the gut microbiota in the disease development [27,28,104,105] and a recent published review concluded that the altered abundance of specific members or reduced diversity of gut microbiota was associated with the progression of T1D [106].…”
Section: Gut Microbiotamentioning
confidence: 99%